ON DESIGNING AN INFORMATION SYSTEM APPLIED FOR THE COMMERCIAL COMPANIES - Russel A. Hassan; Yaser A. Jasim; Nurul Izzah Lubis; Ali Jalal Awqati (LPPM Univ Potensi Utama, 2020)
This paper attempts to study the designing of the accounting information system to be used and applied in commercial companies. Therefore, the principal and fundamental aim and objective of this paper are to give the best approaches and techniques of modeling a good, robust, and reliable accounting information system that focuses on Transaction Processing System, General Ledger, Financial Reporting System and Management Reporting System in the commercial company. The researchers designed the main charts of the system that will help in the construction of an ideal and robust Accounting Information System (AIS), with the simple and lowest cost methods, techniques, and approaches. In addition, the practical section in this paper depicts the accounts of the company, the financial statements, invoice, income statement, balance sheet, assets, liabilities and the important factor is the relationship between the accounts. The proposed information system is designed to be flexible to suite most of the commercial companies due to the difference among each of them. Therefore, after applying it the information system showed a great relation between accounts. The main conclusion of this paper is that the analyzing and designing process of an accounting information system (AIS) needs a good knowledge about the commercial environment that surrounded the represented company which will be as wisdom in knowledge representation science.